Glaciations at high-latitude Southern Australia during the Early Cretaceous. Issue 8 (16th November 2020) - Alley, N. F.; Hore, S. B.; Frakes, L. A.
Abstract: Stratigraphic investigations, supported by palynological dating, detrital zircon and monazite dating, and quartz grain micromorphology were undertaken of the Early Cretaceous strata around the southern margin of the Eromanga Basin where they onlap older rocks of the northern Flinders Ranges. The presence of a tillite within the Early Cretaceous Cadna-owie Formation and another in the Trinity Well Sandstone are evidence of two significant glaciations: the oldest, the Livingston Tillite Member, is from the middle Valanginian; the younger, the Sheehan Tillite Member, is from the early Aptian. A significant hiatus encompassing the Barremian interrupts the succession. Extensive dropstones, minor diamictite lenses and beds and a bed containing glendonite crystals, together indicate that cold (limited glacial and/or seasonal freezing) conditions persisted through the Hauterivian and the Aptian, with cold conditions peaking in the late Aptian.